Site selection and design of big data centers - HUANG Junya; ZHAO Ming; YAN Jin; ZHENG Zhi (Dianxin kexue, 2025)
The major factors influencing the selection of locations for big data centers were firstly analyzed, with a focus on the issues of site selection and scale planning. Based on expert evaluations, a site selection evaluation model was constructed using the analytic hierarchy process (AHP), resulting in the establishment of general evaluation criteria. Subsequently, an investigation was conducted among 48 key cities nationwide according to the site selection evaluation model, yielding an overall score and ranking for each city. Further analysis was carried out on the elements of scale design for big data centers, leading to the proposition of a scale design model. The aim of this process is to provide a reference for the construction and deployment of big data centers.